Sustainable Development in Consulting Firms: The Links between CSR and Company's Performance - Yang, Yun (2012)
It takes decades for the researchers to define the CSR in a comprehensive way because CSR is really a vague concept. It has become a hot topic currently however few researches were conducted in consulting area. In this paper, more research data would be collected from consulting firms through interviews and documentaries. In order to show people what CSR looks like in consulting area, Consulting industry is a special industry because it provide other industries with advises. The main focus of this paper is to find the answer for the research question: “How does CSR affect company’ performance?” Using ground theory as a background, some current theories were generated, this research would show you the factors that affect CSR behaviors and the new frameworks of CSR , then compared with existed theory, a conclusion were made that CSR had low impact on company’s performance. The limitations of this research were also clarified in this paper, mainly concentrated on the data collection.